Klebsiella variicola improves the antioxidant ability of maize seedlings under saline-alkali stress - Lijuan Yang; Yufeng Wang; Kejun Yang (PeerJ, 2021)
Background Saline-alkali soil is mainly distributed in the northern and coastal areas of China. The Songnen Plain, located in the northeast of China, is a region with a relatively high concentration of saline-alkali soil and is also one of the more at-risk areas in the country. Every year, the increasing spread of saline-alkali soil areas has a serious impact on the growth of agricultural crops. The maize crop is sensitive to saline-alkali stress, which seriously affects its growth and development. Our previous study determined that Klebsiella variicola performs a variety of biological functions, as well as improves the rhizosphere microenvironment and promotes the growth and development of maize seedlings in saline-alkali soil environments. The present study further analyzed the mechanism that enables K. variicola to alleviate saline-alkali stress at the level of the antioxidant system. Methods The accumulation of O2− was observed directly via histochemical staining. The activities of several antioxidant enzymes were determined using the nitro blue tetrazolium and the guaiacol methods. The contents of non-enzymatic antioxidants were determined using the dithionitrobenzoic acid method. Results The contents of the superoxide anion and hydrogen peroxide in leaves and roots of maize seedlings increased under saline-alkali stress conditions. The higher level of reactive oxygen species increased the degree of membrane lipid peroxidation. There were differences in the degree of oxidative damage and performance of the antioxidant defence system in maize seedlings under saline-alkali stress. Following the application of increasing concentrations of K. variicola, the activity of antioxidant enzymes increased by 21.22%–215.46%, and the content of non-enzymatic antioxidants increased as well, the ratios of ASA/DHA and GSH/GSSG in leaves increased by 4.97% and 1.87 times, respectively, and those in roots increased by 3.24% and 1.60 times, respectively. The accumulation of reactive oxygen species was reduced, and the content of H2O2 decreased by 26.07%–46.97%. The content of O2− decreased by 20.18%–37.01%, which alleviated the oxidative damage to maize seedlings caused by saline-alkali stress. Conclusion K. variicola reduced ROS-induced peroxidation to membrane lipids and effectively alleviated the damage caused by saline-alkali stress by increasing the activities of antioxidant enzymes in maize seedlings, thus enhancing their saline-alkali tolerance. A bacterial concentration of 1×108 cfu/mL was optimal in each set of experiments.